Thymus vulgaris L (thyme) essential oil and its combination with EDTA against Candida albicans; formulation of a cream - Rojas Armas, Juan (2015)
Introduction: Candida albicans may cause severe invasive infections and frequently superficial lesions. Drugs used in treatment present drawbacks and search of alternatives becomes necessary. Objectives: To determine the activity of Thymus vulgaris essential oil (EO) alone and combined with EDTA on Candida albicans, and formulate a cream with EO supplemented with natural terpenes. Design:In vitro experimental and in vivo toxicity study. Setting: Faculty of Medicine and Faculty of Pharmacy, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological material:Candida albicans strain for in vitro study and rabbits for dermal toxicity tests. Methods:Antifungal activity was determined by agar well diffusion method, and minimum inhibitory concentration (MIC) by broth microdilution method. A cream was formulated with EO 1% and another supplemented with carvacrol, thymol, citral and EDTA. Dermal toxicity in rabbits was determined. Main outcome measures: Inhibition halos, MIC, signs of toxicity. Results: EO at 100 mg/mL inhibited Candida albicans growth with 30.33 ± 0.58 mm inhibition halos; adding EDTA produced 35.33 ± 0.58 mm halos. MIC for EO and EO + EDTA was respectively 8 mg/mL and 0.5 mg/mL. EO 1% cream originated 13.33 ± 0.58 mm inhibition halos, and addition of EDTA, thymol, carvacrol and citral increased halos to 24.33 ± 0.58 mm. No signs of dermal toxicity in rabbits were observed. Conclusions:Thymus vulgaris EO showed inhibitory activity against Candida albicans and EDTA increased this activity; essential oil, EDTA, carvacrol, thymol and citral formulated in cream also showed synergistic effect without evidence of dermal toxicity.